2022
DOI: 10.1038/s41598-022-14273-z
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive and non-disruptive detection of residual undifferentiated cells by measuring miRNAs in culture supernatant

Abstract: The clinical usage of induced pluripotent stem cell (iPSC)-derived regenerative medicine products is limited by the possibility of residual undifferentiated cells forming tumours after transplantation. Most of the existing quality control tests involve crushing of cells. As a result, the cells to be transplanted cannot be directly tested, thereby increasing the cost of transplantation. Therefore, we tested a highly sensitive and non-disruptive quality-testing method that involves measuring microRNAs (miRNAs) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…In order to improve the sensitivity, we built an assay based on ddPCR platform using TaqMan probe and found that the expression of target miRNAs in hCiPSC-islets was too high to discriminate subtle transcripts of hCiPSCs (data not shown). We also tried to isolate miRNAs from cell culture supernatant which was showed to be an efficient method for detecting miRNAs 42 , 43 , but still could not reach enough detection sensitivity. This illustrates the pivotal role in selecting a proper biomarker for detecting specific iPSC derived cell product.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the sensitivity, we built an assay based on ddPCR platform using TaqMan probe and found that the expression of target miRNAs in hCiPSC-islets was too high to discriminate subtle transcripts of hCiPSCs (data not shown). We also tried to isolate miRNAs from cell culture supernatant which was showed to be an efficient method for detecting miRNAs 42 , 43 , but still could not reach enough detection sensitivity. This illustrates the pivotal role in selecting a proper biomarker for detecting specific iPSC derived cell product.…”
Section: Discussionmentioning
confidence: 99%
“…However, hPSCs are intrinsically tumorigenic and form teratomas [ 1 , 2 ]; therefore, the establishment of a robust and internationally harmonized methodology to evaluate the contamination of products with residual undifferentiated hPSCs is critically beneficial, not only for product developers but also for regulatory authorities and patients [ 1 , 3 ]. Among the currently available in vitro testing methodologies [ [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] ] which are based on flow cytometry [ 4 ], enzyme-linked immunosorbent assay-like sandwich assay [ 5 ], quantitative RT-PCR [ 4 , 6 ], droplet digital PCR (ddPCR) [ [7] , [8] , [9] ], reverse transcription loop-mediated isothermal amplification [ 10 ], and highly efficient culture (HEC) system [ 11 ], the HEC assay is one of the most robust and sensitive assays that can directly detect hPSCs by identifying hPSC-derived colonies under culture conditions that favor their growth [ 11 ].…”
Section: Introductionmentioning
confidence: 99%